Effect of Acupuncture on Gut-Brain Axis Parameters in Patients with Atopic Dermatitis: A Study Protocol for a Randomized, Participant- and Assessor-Blind, Sham-Controlled Trial. (6th September 2021) - Kim, Jundong; Kwon, Soon-Kyeong; Lee, In-Seon; Yeom, Mijung; Hahm, Dae-Hyun; Park, Hi-Joon; Kim, Kyuseok
Abstract : Atopic dermatitis (AD) is a relapsing and remitting chronic inflammatory skin disease for which a variety of etiological factors are involved. Treatment strategies should be multifaceted and have few side effects. In this respect, acupuncture has become increasingly popular as a safe, consistently effective, and drug-free therapy that treats multiple AD symptoms. We aim to not only verify the effectiveness of acupuncture but also suggest patient-specific response determinants and a new underlying mechanism implicating the gut-brain axis. We have designed a randomized, participant-blinded, sham-controlled clinical trial for 60 mild to moderate AD patients. In a previous study, we observed that the clinical skin symptoms of AD were closely associated with gastrointestinal (GI) symptoms. From these findings, we developed an intervention with six acupuncture points: three for AD symptoms and three for GI symptoms. Also, since high responders and low responders to the acupuncture treatment could be identified in the previous study, we now aim to explore response-determining factors, with a particular focus on GI symptoms. Therefore, we will precisely evaluate not only AD symptoms using the SCORAD, EASI, and DLQI tools, but also GI symptoms using the GSRS, TDS, BSFS, and AR tools and abdominal examination. AD develops in association with complicated pathophysiological factors, such as skin barrier function, genetic susceptibility, and immunological factors. Moreover, the underlying mechanism by which acupuncture treatment works has not been clearly elucidated. We, therefore, will conduct a simultaneous cross-sectional study with a sample of 40 healthy individuals, wherein potential indicators, such as fMRI, gut microbiota, and serum TARC and ATX, will be investigated to determine the gut-brain axis-associated mechanism of acupuncture. We expect that the results of this study could provide important clinical evidence for the effects of acupuncture and help elucidate the therapeutic mechanisms that underlie acupuncture's efficacy in AD treatment. This trial is registered with https://clinicaltrials.gov/ct2/show/KCT0005422 (Trial registration: Korean Clinical Trial Registry (http://cris.nih.go.kr; registration number: KCT0005422); date of registration: September 23, 2020).